Evolutionism, Relativism and Putting Native People into Historical Context - Trigger, Bruce G. (Culture, 1986)
What is the relevance of the seemingly antithetical views of cultural evolutionism and cultural relativism for the study of native history ? Despite the important role of epidemic diseases in weakening the capacity of native people to oppose early European domination, the technological gap between the two groups of societies, together with associated differences in social organization and values, played a significant role in making European domination possible. Native cultures were not adapted to coping with European ones. Yet the human capacity for rational calculation was not affected by cultural differences. Native people, both as individuals and as groups, displayed no less ingenuity than did Europeans in responding to the challenge of cultural contact. Despite severe deprivation they have gradually articulated the knowledge and sense of direction required to compete for a fairer share of North America’s resources.